2016
DOI: 10.1002/ehf2.12082
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure from heart muscle disease in childhood: a 5–10 year follow‐up study in the UK and Ireland

Abstract: AimsOur original study, the first national prospective study of new‐onset heart failure from heart muscle disease in children, showed overall 1‐year survival of 82%, and event (death or transplantation)‐free survival of 66%. This study aimed to evaluate 5 + year outcomes of this important cohort.Methods and resultsAll centres in the UK and Ireland with 1‐year event‐free survivors participated (n = 14). Anonymised data based on last hospital attendance and echocardiograms were reviewed. The investigator was bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…103, 104 Registries from the U.S., Australia, and Europe report transplant-free survival rates ranging from 60% to 75% within five years after diagnosis, with most events occurring within two years of presentation. 4, 10, 15, 105107 These same registries also report that 20% to 45% of patients regain normal cardiac function during the same time period. 4, 10, 103, 105, 106 …”
Section: Dilated Cardiomyopathymentioning
confidence: 80%
“…103, 104 Registries from the U.S., Australia, and Europe report transplant-free survival rates ranging from 60% to 75% within five years after diagnosis, with most events occurring within two years of presentation. 4, 10, 15, 105107 These same registries also report that 20% to 45% of patients regain normal cardiac function during the same time period. 4, 10, 103, 105, 106 …”
Section: Dilated Cardiomyopathymentioning
confidence: 80%
“…In the previously mentioned prospective study of 104 children who presented with a first episode of heart failure, which was carried out in 2003, 12% required extracorporeal membrane oxygenation (ECMO) support but, as far as we can determine, none received a VAD as part of the initial presentation. 14 A follow-up report on this cohort 23 showed that 44 (42%) had normal function on echocardiogram at a median followup of 9 years and that 50% of these were on no medication. There are also data to show that children with a diagnosis of idiopathic dilated cardiomyopathy may show late recovery of function.…”
Section: Discussionmentioning
confidence: 92%
“…Other recognized causes are toxic and genetic (52,53). Data show that 20% of children diagnosed with DCM normalize their systolic function within 2 years; whereas 40% die or undergo heart transplantation (54)(55)(56)(57)(58). In patients with neuromuscular, metabolic or mitochondrial disorders the underlying disease is an important determinant of outcome (1,3,59).…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%